Soil properties, carbon composition, microbial community, and potential CO2 production from a typical thaw slump on the northern Qinghai-Tibet Plateau - Mei Mu; Cuicui Mu (PANGAEA, 2025)
Rapid warming of permafrost regions leads to the widespread development of thaw slumps and accelerates the decomposition and release of soil organic carbon. Yet, how the evolution of thaw slump affects carbon dioxide (CO2) release remains unclear. This dataset presents soil properties, carbon composition, microbial community, and potential CO2 production from a typical thaw slump located in the northeastern Qinghai-Tibet Plateau (37°28'N, 100°17'E, 3597m). In the field, we set up a control area and three collapse areas (including 1, 12, and 23 years of collapse) along the thaw sequence. In each plot, we set up three quadrats (~4 m exttimes 5 m) along a diagonal line. Three replicates of topsoil (0–15 cm) and subsoil (15–30 cm) were collected from each quadrate and mixed by depth as one composite sample for subsequent analyses. The soil sampling was carried out in July 2020. Each of the collected soil samples was divided into three subsamples after sieving (2-mm mesh) and removal of stones, root fragments, and plant material. The first subsample was stored at -80 °C for biomarker phospholipid fatty acids (PLFAs) and enzyme activities analysis, the second subsample used laboratory incubation, and the third subsample was air-dried to determine soil physical and chemical properties, including soil moisture, texture, pH, SOC content, total nitrogen content, stable carbon isotopes, and carbon composition; this data is presented here. All samples were further analyzed for potential CO2 production rate and cumulative CO2 release using aerobic incubations for 189 days at 10 °C.